The Influence Of Academic Perfectionism And Religion On The Mental Health Of Students In Islamic Higher Education - Anwar, Mazyunatul Filzah; Putra, Pristian Hadi (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam Universitas Islam Malang, 2025)
Many students set high standards for themselves such as having a high GPA and perfect grades in lectures. This triggers the emergence of perfectionism in themselves so that it can become excessive pressure that affects students' mental health. This study aims to investigate the effect of academic perfectionism and religious perfectionism on the mental health of PAI students in Kerinci State Islamic Institute both individually and simultaneously. The method used in this research is quantitative by using multiple regression analysis techniques with a sample of PAI students in Kerinci State Islamic Institute. The results showed that there was no effect of academic perfectionism on the mental health of PAI students and there was no effect of religious perfectionism on the mental health of PAI students. Simultaneously, academic perfectionism and religious perfectionism did not affect the mental health of PAI students. However, this study found a relationship between academic perfectionism and religious perfectionism. This suggests that other factors may play a greater role in influencing the mental health of PAI students at Kerinci State Islamic Institute.